Layanan Psikoedukasi sebagai Upaya untuk Mencegah Toxic Relationship Pada Remaja di MAN 3 Sleman - Salsabilla; Azzahra Aulia Muharram; Barirotul ‘Aizza Salsabila; Siti Rahmah Muflihatul Jannah (Altruism: The Indonesian Journal of Community Engagement, 2023)
Toxic relationships are considered unwanted relationships, when the relationship no longer provides comfort between the two people. Toxic relationships can drain thoughts and time so that they have a negative impact on adolescent health both physically and mentally, so education for adolescents is needed so that they are not trapped in toxic relationships and avoid toxic relationships. The implementation of community service activities through psychoeducational services in the form of seminars as a preventive effort for toxic relationships in the MAN 3 Sleman environment which was held on Thursday, October 19, 2023. Education related to toxic relationships is very important for Madrasah Aliyah Negeri 3 Sleman Yogyakarta students in particular and all students from various levels in Indonesia in general. This happens because toxic relationships today can not only occur in romantic relationships but friendships can even occur in families. From the results of the SWOT matrix conducted, the provision of this service is carried out so that students also need to understand the criteria for good relationships with partners, siblings, parents and healthy friendships through empathy, active listening, sincerity and unconditional acceptance. Providing psychoeducational services as a madrasah effort to prevent and reduce toxic relationship behavior, it is hoped that MAN 3 Sleman students are more aware that knowledge about toxic relationships is very important to pay attention to.